Status of essential elements in autism spectrum disorder: systematic review and meta-analysis - Saghazadeh, Amene; Ahangari, Narges; Hendi, Kasra; Saleh, Fatemeh; Rezaei, Nima (Reviews in the neurosciences, 2017)
Autism spectrum disorder (ASD) is a lifelong neurodevelopmental disorder that imposes heavy financial burden on governments and families of affected children. It is considered a multifactorial condition, where trace elements are among environmental factors that may contribute to ASD. Meanwhile, the between-study variance is high. The present systematic review was designed to investigate the difference in trace element measures between patients with ASD and control subjects. Meta-analyses showed that the hair concentrations of chromium ( =0.024), cobalt ( =0.012), iodine ( =0.000), iron ( =0.017), and magnesium ( =0.007) in ASD patients were significantly lower than those of control subjects, while there were higher magnesium levels in the hair of ASD patients compared to that of controls ( =0.010). Patients with ASD had higher blood levels of copper ( =0.000) and lower levels of zinc compared to controls ( =0.021). Further urinary iodine levels in patients with ASD were decreased in comparison with controls ( =0.026). Sensitivity analyses showed that ASD patients in non-Asian but not in Asian countries had lower hair concentrations of chromium compared to controls. Also, such analyses indicated that ASD patients in Asian countries had lower hair zinc concentrations, whereas ASD patients in non-Asian countries had higher hair zinc concentrations in comparison with control subjects. This study found significant differences in the content of trace elements between patients with ASD compared to controls. The findings help highlighting the role of trace elements as environmental factors in the etiology of ASD.